Study on Purchasing Behavior of Tampons and Influencing Factors via Mobile E-Commerce in Jiangsu, China - Xie, Dongmei; Thanathanchuchot , Thanakorn (Journal of Dhamma for Life, 2024)
Most girls will have menstrual period every month. From the end of the last century to the early days of Taobao, most female consumers can only go to the supermarket to buy sanitary napkins or similar products. Due to the differences in Chinese and Westerncultural differences, Chinese female consumers are when the cashiers check out, they even feel shy because they buy sanitary napkins. With the rapid development of mobile e-commerce, consumers no longer have to face the awkward situation before. Without leaving home, they can choose their own sanitary napkins and similar products according to their preferences easily. Due to the excessive demand for women’s morality and the subjective prejudice against tampons, only a few shopping malls have publicly sold tampons in China. Therefore, it is still mainly selling online platforms.Therefore, this paper takes mobile e-commerce as background, combines relevant literature and materials, and analyzes the interview method and questionnaire survey method to study decision process and influencing factors of the current consumer when purchasing the tampons through the mobile terminals. Research plan launched on November 2022, with a period of about five months. According to the research, the decision-making process of Chinese consumers when purchasing tampons through mobile terminals is as follows: Problem Recognition, Information Research, Alternative Evaluation, Purchase Decision, Order Process, Parcel Reception,Post-sale Service, Post-purchase Evaluation, Repeated Consumption. And have 10 independent variable factors that affect the decision-making process, which are: personal factors, Reference Group, Price, Culture, Brand, Ease of Use, Website Design, Orders’ Privacy Protection, Security while Online shopping and Merchants’ Profile & Credibility. In the end, according to the results of this paper, we made suggestions on the market status and consumer concepts to adjust and improve to better meet the needs of Chinese female consumers.